Asuhan Keperawatan Keluarga Pada Tahap Perkembangan Lanjut Usia Dengan Intervensi Terapi Foot Massage Untuk Menurunkan Tekanan Darah Pada Ny. Y. Di Kampung Bayur Rt 003/004 Kel. Periuk Jaya Kota Tangerang - Fitria Handayani; Alfika Safitri; Rina Puspita Sari; Muhammad Hasan Basri (Lembaga Pengembangan Kinerja Dosen, 2023)
Introduction at Hypertension is a non-communicable disease which is a family health problem because it causes adverse effects. The family as a subsystem that is the goal of public health care has a duty to maintain the health of its members, including the management of hypertension in the family. The purpose of writing is to provide an overview of providing family nursing care with foot massage interventions to reduce blood pressure in hypertension. The method used with the family nursing care process which consists of assessment, nursing diagnosis, intervention, implementation, and evaluation. The results show that family nursing problems that arise are pain, ineffective family health maintenance, and sleep pattern disturbances. The implementation results show that foot massage therapy can reduce pain and reduce blood pressure in hypertensive patients from 180/90 mmHg to 150/85 mmHg after three days of foot massage therapy. Nurses can provide foot massage exercises to family members to deal with hypertension in providing family nursing care.